Part 2 of the 11+ as an effective home-based exercise programme in elite academy football (soccer) players: a one-club matched-paired randomised controlled trial - Veith, S.; Whalan, M.; Williams, S.; Colyer, S.; Sampson, J. A. (Science and Medicine in Football, 2021)
Background:Although the 11+ is known to reduce injuries and improve performance in adolescent footballers, its duration presents a notable barrier to implementation. Hence, this study investigated injury and performance outcomes when 65 elite male academy footballers either performed Part 2 3x/ week at training (TG) or at home (HG). Methods:Time to stabilisation (TTS), eccentric hamstring strength (EH-S) and countermovement jump height (CMJ-H) were collected 4 times during the 2019 football season. Linear mixed models were used to evaluate main and interaction effects of group and time. Bonferroni post-hoc tests were used to account for multiple comparisons. Differences in time loss and medical attention injuries were determined using a two-tailed Z test for a comparison of rates. Results:Relative to baseline, EH-S (HG 4.3 kg, 95% CI 3 to 5.7, p < 0.001; TG 5.5 kg, 95% CI 4.3 to 6.6, p < 0.001) and CMJ-H (HG 3.5 cm, 95% CI 2.2 to 4.7, p < 0.001; TG 3.2 cm, 95% CI 2.2 to 4.3, p < 0.001) increased, with no difference between groups observed at the end of the season. All injury outcomes were similar. Conclusion: Rescheduling Part 2 did not affect performance or increased injury risks in academy footballers.